FUNCTIONAL CHARACTERISTICS OF LINGUISTIC AND STYLISTIC MEANS OF EMOTIONAL IMPACT IN POLITICAL DISCOURSE - Yuliia Ovchar (Інтегровані комунікації, 2025)
The study is devoted to a comprehensive analysis of the functional characteristics of linguistic and stylistic means of emotional influence that function in the modern political discourse of the information space, forming political narratives to achieve emotional influence on the audience. The relevance of the study is accompanied by modern communication theory, which allows for a deep analysis of the influence of the media on human consciousness and the characteristics of the functional features of linguistic and stylistic means of emotional influence in political discourse. The purpose of the study is to analyze the functional characteristics of linguistic and stylistic means used for emotional influence in political discourse and to determine their role in the formation of public opinion and political behavior. The task of the study is to describe the functional features of the identified linguistic and stylistic means and to determine the contextual factors that determine the effectiveness of the use of various linguistic and stylistic means of emotional influence in political discourse. The study used the following research methods: analysis of scientific literature, content analysis, discourse analysis, and comparative analysis.